TOURISM AS A TOOL FOR ENGLISH LANGUAGE ACQUISITION - Mukharramkhon, Numonova; Pаrizodа, Mirboboyevа (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This research examines the role of tourism as a dynamic tool in the acquisition of the English language, focusing on how it can develop linguistic competence through direct contact. It also explores how travel enhances real-world language use, cultural interaction, and practical communication skills. The paper reviews case studies on the experiential learning process of language learners who are engaged in tourism-related activities for illustrating efficacy within a range of hostels, guided tours, and cultural events. A review of the obstacles which tourism poses in enhancing this competency, including such impediments as socio-cultural exchange or/and technology integration. The findings prove that tourism enhances not only language acquisition but also cultural awareness of learners, for which it needs to be included in contemporary English language education. The study also recommended that language education involve efforts related to tourism for an increase in authentic language use and engagement.